Hordeetum murini Libbert, 1932 - A ruderal association in Kosovo - Qazim PAJAZITAJ (Acta Agriculturae Slovenica)
The paper deals with the vegetation of the association Hordeetum murini Libbert 1932 (Sisymbrietalia, Sisymbrion) in Kosovo. It is one of six ruderal communities studied in Kosovo during 1988 - 1991. The association Hordeetum murini is a ruderal vegetation that appears later in the spring and disappear in the beginning of the summer. This association is well developed in all habitats of Kosovo. This paper deals with the floristic and syntaxonomic analysis of association (Table 1), which encapsulates 12 relevés out of 62 species. It was also analyzed the biological spectrum of association, and symbols of life forms of each species. Also, in the analysis of floral geoelements, groups of these elements have been determined and presented by its spectrum.